Estudo bibliográfico da avaliação formativa em contexto de ensino não presencial mediado por tecnologias digitais de informação e comunicação (TDICs) - Goes, Lucas Serniker de Melo (Universidade Federal de São Carlos, 2023)
In January 2020, the World Health Organization (WHO) declared that the outbreak of the new coronavirus constituted a Public Health Emergency of International Concern (PHEIC). At the national level, and specifically in the area of education, the SARS-CoV-2 pandemic created challenges and required immediate changes, including the suspension of presential activities and adherence to the denominated emergency remote teaching (ERT). In this context, several processes were questioned, including the evaluation. Although the ERT was unprecedented, the experiences in distance learning in Brazil were not, which intrigued us to understand whether alternatives to what was experienced would not be part of the knowledge of the area. In this sense, and based on the premise that formative assessment processes are the most appropriate for enhancing learning, we ask ourselves: "What formative assessment instruments or strategies can be observed in non-face-to-face teaching experiences recorded in the academic literature of the educational area?". Based on this guiding question, this investigation intends to analyze the dimension of evaluation in non-face-to-face teaching experiences documented by the literature of the area, with the intention of understanding if and how the formative dimension of evaluation is present in these experiences. Considering the need to develop research that does not limit the concept of knowledge to isolated data, this investigation was based on a qualitative approach and used documental sources through bibliographical research as a methodological procedure. In this sense, we defined the data production technique as an interpretative analysis of selected academic productions. This bibliographical research is constituted of a wide bibliographical survey of articles, theses and dissertations published nationally between the years 1996 and 2021 (from the regulation of Distance Education in the ‘Lei de Diretrizes e Bases’ until the beginning of the pandemic period) about the formative assessment process proposed in non-face-to-face. In this way, it was intended to contribute to the advancement of discussions on formative assessment. In conclusion, it was possible to observe that the instruments and the FA strategies present in the experiences are diverse, however it was possible to verify characteristics that unify them, such as the recognition of making constant adjustments and the appreciation of student interaction. In addition, we understand that successful experiences with FA are generally linked to the continuous observation of the principles of investigation, intervention and inclusion, being necessary to contrast — based on these elements — what has been practiced and what is intended to be achieved.
Bibliographic study of formative assessment in the context of non-face-to-face mediated by digital information and communication technologies (DICTs)
Keywords: Avaliação formativa; Ensino não presencial; Educação a distância; Ensino remoto emergencial; Estudo bibliográfico; Formative assessment; Distance learning; Distance education; Emergency remote teaching; Bibliographic study; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM